Brazil: radicalization of the political process (2013–2019) - L. S. Okuneva (Ибероамериканские тетради, 2019)
The   article is  devoted  to  the  analysis of  such an  important trend  in the   development  of  the   political process  in  modern Brazil as  radicalization and polarization. These trends began to appear even  from  the  mass social movements of 2013, gradually gained strength, and became decisive in  the  series of  presidential elections in  2014 and 2018 and are now  the  main trend of  Brazilian  politics. The release  of  prison in  November 2019  and the  inclusion  in  the  political  live  of  the former president Luíz  Inácio Lula da Silva, the  largest leftist Brazilian politician, can give  a special impetus to political radicalization.